A Reference Lexicon Definition from Fact Models. Issue 3 (2015) - Andrade, Pedro; Sarraipa, Joao; Jardim-Goncalves, Ricardo
Abstract: Nowadays, it has been noticed an increased demand for interoperable systems capable of exchanging information within collaborative business environments. Consequently, cooperation agreements between each of the involved enterprises have been brought to light. However, due to the fact that even in a same community or domain, there are a big variety of business concept models that are not semantically coincident, which embodies the need of an enterprise reference lexicon definition for interoperable communications establishment. This paper proposes an approach that addresses the automation in the information models mapping and the reference lexicon construction. It aggregates a formal and conceptual representation of the business domain, with a clear definition of the used lexicon to facilitate a further and overall understanding of the business model.